A Novel Strategy as a Potential Rapid Therapy Modality in the Treatment of Corneal Ulcers: Fluconazole/Vancomycin Dual Drug‐Loaded Nanofibrous Patches - Sumeyye Cesur; Elif Ilhan; Esra Pilavci; Rabia Betul Sulutas; Merve Gurboga; Ozlem Bingol Ozakpinar; Elif Kaya; Marcin Heljak; Gulgun Bosgelmez Tinaz; Faik Nuzhet Oktar; Oguzhan Gunduz; Ewa Kijeńska‐Gawrońska (Macromolecular Materials and Engineering, 2023)
Abstract Corneal ulcer, which is brought on by a breach in the epithelial barrier, is a dangerous infection of the avascular corneal stroma. New treatment strategies are needed, suppressing the aggressive nature of the disease and including a combination of different drugs. In this study, vancomycin (VAN) and fluconazole (FLU) dual‐drug loaded dual‐layered polyvinyl alcohol and gelatin (PVA/GEL) nanofibrous patches are produced by electrospinning. Scanning electron microscopy (SEM) images show smooth surfaces are obtained for both pure and drug‐loaded nanofibrous patches. The tensile test results report that loading the FLU and VAN separately into the PVA/GEL patches decrease both the tensile strength and elongation at break and it is further reduced when combining two drug‐loaded layers in one patch. According to drug release results, the FLU and VAN‐loaded nanofibrous patches show a controlled release profile extending up to 96 h. Moreover, PVA/GEL/FLU, PVA/GEL/VAN, and PVA/GEL/FLU/VAN nanofibrous patches display significant antimicrobial activity against Candida albicans and Staphylococcus aureus. SEM, 4'‐6diamidynofenyloindol (DAPI) staining, and 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) assay show that PVA/FLU and PVA/GEL/FLU/VAN nanofibrous patches have a superior effect on NIH3T3 cell spreading and proliferation. The novelty of this study lays in the development of a potential dual drug rapid treatment for corneal ulcers of aggressive nature.